Unveiling Job Satisfaction: A Comprehensive Study of Teaching Staff at a Sudanese University - Amel Farage Rmadan (Nurul Jadid University, 2022)
The purpose of this study was to assess the level of job satisfaction among teaching staffs at Gezira University, and to analyze gender differences in the level of job satisfaction among the staff of the Gezira University. The study employed survey research approach by using a questionnaire developed from the Minnesota Satisfaction Questionnaire (MSQ) and Lester (1987) Teacher Job Satisfaction Questionnaire (TJSQ). 209 participants were taken through simple random sampling techniques. The results indicate that the staffs of the Gezira University are satisfied with promotion and supervision and coworkers system. The staffs of the Gezira University demonstrate low level in work itself, pay, and work condition dimensions of job satisfaction. The study found no statistically significant difference between the male and female groups in the level of job satisfaction in the Gezira University. The study also indicates that there is no difference in the level of job satisfaction related to academic rank in the Gezira University. The study recommended that the Gezira University must improve the work condition for the staff by providing work facilities and improving the work environment as whole.